Pengunaan Hijab Cosplay Perspektif Fikih Wanita: The Use of Cosplay Hijab in The Perspective of Islamic Jurisprudence for Women - Putri Indiarti Saleng; Jujuri Perdamaian Dunia; Rahmayani Lancang (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The study aims to investigate the phenomenon of hijab cosplay from the perspective of women's fiqh, where Muslim women integrate the hijab into their cosplay costumes. The research method used is qualitative descriptive with a normative (shar'i) and phenomenological approach. The results of the study indicate that hijab cosplay involves creative modifications to the hijab fabric and costumes to comply with Islamic rules of covering, according to women's fiqh perspectives, without sacrificing the character's dentity being cosplayed. The findings show the importance of adhering to Islamic law in the use of hijab in cosplay activities. Hijab cosplay is a form of Muslim women's creativity in expressing their cosplay hobby through costume modifications based on fanart or personal creations. Hijabi cosplayers can transform the appearance of non-hijabi characters to comply with the rules of women's covering. However, despite showing creativity in modifying hijabs and costumes, hijab cosplay often does not meet the correct hijab requirements and involves the use of conspicuous accessories.In cosplay events, the interaction between hijabi cosplayers and men that does not conform to sharia boundaries, as well as the use of conspicuous fragrances, indicates a violation of the values of modesty. Additionally, seeking popularity through syuhroh clothing reflects behavior that does not embody the essence of the hijab as a symbol of modesty and obedience. Therefore, the use of hijab cosplay is prohibited because it does not meet the requirements of hijab from the perspective of women's fiqh.